An adapted mindfulness intervention for people with dementia in care homes: feasibility pilot study. (7th February 2017) - Churcher Clarke, A.; Chan, J.M.Y.; Stott, J.; Royan, L.; Spector, A.
Abstract : Objective: Depression and anxiety are common in dementia. There is a need to develop effective psychosocial interventions. This study sought to develop a group‐based adapted mindfulness programme for people with mild to moderate dementia in care homes and to determine its feasibility and potential benefits. Methods: A manual for a 10‐session intervention was developed. Participants were randomly allocated to the intervention plus treatment as usual ( n  = 20) or treatment as usual ( n  = 11). Measures of mood, anxiety, quality of life, cognitive function, stress and mindfulness were administered at baseline and 1 week post‐intervention. Results: There was a significant improvement in quality of life in the intervention group compared to controls ( p  = 0.05). There were no significant changes in other outcomes. Conclusions: The intervention was feasible in terms of recruitment, retention, attrition and acceptability and was associated with significant positive changes in quality of life. A fully powered randomised controlled trial is required. Copyright © 2017 John Wiley & Sons, Ltd.